Silent inflammation: a hidden cause of liver fibrosis - Schon, Hans-Theo; Weiskirchen, Ralf (Frontiers in Pharmacology, 2026)
Systemic inflammation induced by adipose tissue is common in obese individuals and is often overlooked due to its subclinical nature. The constant secretion of proinflammatory factors shifts the balance toward inflammation, affecting the body’s homeostasis and facilitating the development of various chronic diseases. In the liver, proinflammatory markers, free fatty acids (FFAs), and the hormone leptin, all of which originate from adipose tissue, trigger an inflammatory response that favors fibrogenesis. Conversely, serum levels of proinflammatory factors can be used to assess both the risk of liver fibrosis and the effectiveness of treatment. Their application is straightforward due to their non-invasive nature, but it is important to confirm their reliability in future investigations. Moreover, dietary approaches to therapy, along with physical activity, deserve more attention as their effectiveness has frequently been demonstrated and they are recommended by official guidelines. The focus on reducing body weight through fat loss is especially crucial. To enhance the quality and value of dietary strategies in therapy, it is also necessary to refine and expand their potential.